Design and fabricate of a motorized cutter for mechanical part - Maizatul Mastura, Muhammad Nazri (2008)
Cutter is a common tool used in various cutting shape for a variety purposes. In this project, the improvement of cutter which is design and fabricate of a motorized cutter for mechanical part then integrate the system using a 24V DC motor to operate the system so it can cut the fruit brunches easily without using our own energy too much. This cutter can lift up until 3.5 m and above according the user height and it not too heavy to carry it because it weight is 2.2 kg including the electro-mechanical part. This cutter also safe to used because of the C-sickle is weld properly and tied with aluminum plate together with bolt and nut so it cannot easily falling down to the ground which is can get hurt. The design of this product is suitable with the electro-mechanical part and can work together. The operating for this system is control by the controller to moving the motor spindle. When press the ON button the motor spindle will move clockwise direction then roll the rope while it attract top rod which is it will through the hole until the spring retract is finish. Then, when press the OFF button, the motor spindle will released the rope and the spring will extend back to it normal position. However, this cutter needs to be handled by two persons because one person needs to hold the battery and the controller and the other person will hold the rod. Hence, this motorized cutter can help people to harvesting fruit bunches easily and also can used it in a long term.